The Impact of the Presence of Pattimura University Ambon on the Economic Conditions of the Community in Poka Village, Teluk Ambon District, Ambon City - Lasaiba, Mohammad Amin; Kelderak, Nurwahida (GEOFORUM, 2022)
This study investigates the impact of the presence of Pattimura University in Poka Village on the economic conditions of the surrounding community, with a focus on the boarding house business as one of the emerging economic effects. The research employs a qualitative method with a descriptive approach. Data were collected through observations, interviews, questionnaires, and documentation. The results indicate that the presence of the university has had a positive impact on the economic conditions of the local community, such as increased business opportunities and job prospects. The boarding house business in Poka Village serves as an example of how business opportunities have developed in tandem with the growing student population. This positive impact is reflected in the increased income and well-being of the community. However, there are also negative effects, such as population density and high mobility. This study provides insights into the complex relationship between the presence of a university and local economic development, highlighting the need for wise management to optimize positive impacts and address negative ones.